2003
DOI: 10.1124/mol.63.3.524
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Nuclear Translocation of an Orphan Nuclear Receptor, SXR

Abstract: The steroid and xenobiotic receptor (SXR) is an orphan nuclear receptor that plays a key role in the regulation of xenobiotic response by controlling the expression of drug metabolizing and clearance enzymes. We observed that pregnane X receptor (PXR), the mouse ortholog of SXR, was retained in the cytoplasm of hepatic cells of untreated mice, whereas PXR was translocated to the nucleus after administration of a ligand, pregnenolone 16␣-carbonitrile. To understand the molecular mechanisms underlying the xenoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 39 publications
3
74
1
Order By: Relevance
“…Hence, using PXR antiserum we also investigated the expression of PXR variants in a liver cell line (HepG2) and intestinal adenocarcinoma cell line (COLO) by Western blot analysis. Based on this study, as well as others [20], transfected PXR is observed to be a predominantly nuclear protein. Therefore, we prepared PXR-enriched nuclear extract from cultured cells for our Western blot analyses.…”
Section: Detection Of Pxr In Transfected Mammalian Cells In Culturesupporting
confidence: 82%
See 1 more Smart Citation
“…Hence, using PXR antiserum we also investigated the expression of PXR variants in a liver cell line (HepG2) and intestinal adenocarcinoma cell line (COLO) by Western blot analysis. Based on this study, as well as others [20], transfected PXR is observed to be a predominantly nuclear protein. Therefore, we prepared PXR-enriched nuclear extract from cultured cells for our Western blot analyses.…”
Section: Detection Of Pxr In Transfected Mammalian Cells In Culturesupporting
confidence: 82%
“…Furthermore, endogenously expressed PXR protein has been shown to be localized in cytoplasm of cultured HepG2 cells [21] while it was undetectable in same cell line by other group [17]. When expressed by transfection in cultured cells, ligand-independent nuclear localization was observed [20,22]. On the other hand, 'nuclear extracts' that were prepared from untreated adult male Wistar rats offered nuclease protection in DNase I foot print analysis of rifampicin-responsive region.…”
Section: Fig 8 (A)mentioning
confidence: 99%
“…We found that a basic amino acid rich sequence in the hinge region of LXR a (NLS3) is important for nuclear localization. An analogous sequence in MR [Tanaka et al, 2005], GR [Freedman and Yamamoto, 2004], and SXR [Kawana et al, 2003] binds to importin a. In addition, we identified a basic amino acid rich sequence (NLS4) À12 to À9 amino acids N-terminal of the DBD in both LXR a and LXR b that is important for nuclear localization.…”
Section: Discussionmentioning
confidence: 90%
“…Another nuclear localization sequence (NLS3) has been identified in the hinge region of nuclear receptors including the GR [Picard and Yamamoto, 1987], the AR [Zhou et al, 1994], the SXR [Kawana et al, 2003], and the VDR [Luo et al, 1994]. Analogous regions exist in both LXR a and LXR b (Fig.…”
Section: Mutations In Nls3 Affect Nuclear Localization Of Lxr a But Nmentioning
confidence: 99%
See 1 more Smart Citation